MODERNIZATION OF THE POLITICAL SYSTEM OF RUSSIA: : TARGETS AND PRIORITY DIRECTIONS - R. Fatykhova, Diana; I. Ostroumov, Alexandr; F. Ostroumova, Olga (Gênero & Direito, 2019)
The article examines the issue of modernization of the political system of Russia. Formation of a democratic political system is an integral part of Russia’s modernization strategy. The relevance and objective need to develop an innovative strategy for the modernization of the political sphere of life in Russian society is determined by the inefficiency of existing political institutions, outdated principles, methods, technologies of organization and management, their inconsistency with modern realities, effective resolution of internal problems and global external challenges. The objective meaning of modernization is determined by modern Russian conditions, the nature of issues and contradictions that require their urgent solution.The study purpose is to develop a strategy for the innovative development of the political system of the Russian Federation. Achievement of this goal requires consideration of the basic conditions and contradictions of the modern development of the political system of the Russian Federation, the most important areas and priorities that contribute to its modernization.As a methodological base for the study, the work includes the following approaches and methods: systemic, structural-functional approaches, sociological, logical, historical and comparative methods, as well as analysis of conditions and contradictions that need to be resolved and contribute to the modernization of the political life of modern Russia.As a research result, we came to the following conclusions: 1. Modernization of the political system of the Russian Federation is an objectively necessary process. However, it is not the result of consensus, but a competition between innovators, conservatives and observers. 2. The strategic goal of modernizing the political system of Russian society is to make Russia one of the leading sovereign powers, with a republican democratic form of government, in which a person lives freely and comfortably. 3. Modernization of the political system shall cover the institutional (state, parties), communicative, regulatory and spiritual and ideological subsystems of Russia. 4. The result of democratic modernization of the political system shall be the formation of political institutions that really reflect and express the interests of social groups and strata and contribute to the formation of solidary community. 5. Creation of a system of ideas and values understandable to the majority of the population, and capable of uniting various layers and groups to carry out modernization. 6. As a result of modernization of the political system as a system of determining goals and priorities, the innovative mechanism becomes an inherent attribute of the development of Russian society. This is the strategic goal of modernization in Russia